2013
DOI: 10.1242/jcs.127357
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor Lgl1 forms discrete complexes with NMII-A, and Par6α–aPKCζ that are affected by Lgl1 phosphorylation

Abstract: Non-muscle myosin IIA (NMII-A) and the tumor suppressor lethal giant larvae 1 (Lgl1) play a central role in the polarization of migrating cells. Mammalian Lgl1 interacts directly with NMII-A, inhibiting its ability to assemble into filaments in vitro. Lgl1 also regulates the cellular localization of NMII-A, the maturation of focal adhesions and cell migration. In Drosophila, phosphorylation of Lgl affects its association with the cytoskeleton. Here we show that phosphorylation of mammalian Lgl1 by aPKCf preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…Lgl also binds to Myosin II and negatively regulates Myosin II function in Drosophila and mammalian cells (Strand et al 1994(Strand et al , 1995Betschinger et al 2005). In mammalian cells, a recent study has revealed that Lgl forms alternative complexes with aPKC (PKCζ) or Myosin II and that phosphorylation of Lgl by aPKC affects its ability to inhibit Myosin II filament formation in polarized migrating cells (Dahan et al 2014). In Drosophila the interaction of Lgl with Myosin II has a role in PCP in Drosophila embryo ventral epidermis (Kaplan and Tolwinski 2010); however the function for this regulation in other types of polarity is unclear.…”
Section: The Actin Cytoskeletonmentioning
confidence: 99%
“…Lgl also binds to Myosin II and negatively regulates Myosin II function in Drosophila and mammalian cells (Strand et al 1994(Strand et al , 1995Betschinger et al 2005). In mammalian cells, a recent study has revealed that Lgl forms alternative complexes with aPKC (PKCζ) or Myosin II and that phosphorylation of Lgl by aPKC affects its ability to inhibit Myosin II filament formation in polarized migrating cells (Dahan et al 2014). In Drosophila the interaction of Lgl with Myosin II has a role in PCP in Drosophila embryo ventral epidermis (Kaplan and Tolwinski 2010); however the function for this regulation in other types of polarity is unclear.…”
Section: The Actin Cytoskeletonmentioning
confidence: 99%
“…27 Phosphorylation of Lgl1 by aPKCz affects its cellular localization and prevents its interaction with NMIIA, thus affecting the cellular organization of the acto-NMIIA cytoskeleton. 26 Together, these results strongly indicate that aPKCz plays an important role in cell migration. Nevertheless, little is known about the mechanism by which aPKCz affects cell migration and how it mediates extracellular signals to the cytoskeleton.…”
Section: Introductionmentioning
confidence: 63%
“…We have recently shown that Lgl1 binds NMIIA, inhibiting its ability to form filaments, and that phosphorylation of Lgl1 by aPKCz prevents its interaction with NMIIA both in vitro and in vivo, thus removing the inhibition of NMIIA filament assembly. 26,27 Furthermore, phosphorylation of Lgl1 by aPKCz affects its cellular localization and is important for the cellular organization of the acto-NMII cytoskeleton. 26 We therefore propose that in the absence of aPKCz, Lgl1 is not phosphorylated and binds with NMIIA constitutively, inhibiting its activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations